The Using of Waqf Funds for Childcare Facilities: A Study of Its Permissibility and Implementation - Rameli, Mohd Faizal P.; Amin, Suhaida Mohd; Noor, Abd. Halim Mohd; Mahphoth, Mohd Halim; Salameh, Anas Abdelsatar Mohammad; Othman, Mohamad Khairi Haji (CENTRAL ASIA AND THE CAUCASUS, 2021)
In developed and developing nations including Malaysia, the governments provide financial assistance such as subsidies, tax deductions and financial assistance to help the households with children. However, limited government resources as well as focusing too much on economic growth in the region have restricted the assistance it can provide to the households. Thus, there are many private and charitable sources of funding that exist especially for those in need. For Muslims, there are numerous philanthropic organizations that regularly collect various charitable funds in different forms, such as Zakat, Waqf, Sadaqah, and Hibah. Waqf instrument plays an important role in Muslim societies as its support the aged, the poor, the orphans through provision of education, training and business activities. Waqf institutions have managed to provide social welfare services that many current states struggle to offer. The establishment of Waqf institutions all over the Muslim world was indeed the result of worship towards Allah. This study aims to find out the permissibility of using the Waqf fund for developing of childcare facilities and the best way of its implementation. This study employs a qualitative research methodology based on deductive method of analysis of jurisprudential and literature based-evidences. The conclusion that can be drawn from this research is; Waqf for child care is permissible and can be accomplished through Waqf’s asset integration. This study also proposes the strategies of creation Waqf for childcare facilities through the modification of Waqf fund in few ways.